2015
DOI: 10.5125/jkaoms.2015.41.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life following surgical treatment of oral cancers

Abstract: IntroductionQuality of life (QoL) studies provide information about the impact of disease, the treatment of symptoms, and outcomes following treatment. The present study aims to evaluate the postoperative QoL of patients treated for oral cancer in a Nigerian government tertiary hospital.Materials and MethodsA prospective study on consenting patients with oral cancer was undertaken at Aminu Kano Teaching Hospital, Kano, Nigeria. The subjects completed the University of Washington QoL (UW-QoL) questionnaire one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Efunkoya, et al conducted a study in 2015 to assess the quality of life following surgical treatment of oral cancers [8]. They evaluated the preoperative and postoperative QoL of patients treated for oral cancer in a Nigerian tertiary hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Efunkoya, et al conducted a study in 2015 to assess the quality of life following surgical treatment of oral cancers [8]. They evaluated the preoperative and postoperative QoL of patients treated for oral cancer in a Nigerian tertiary hospital.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Other ancillary unaddressed factors may involve economic strains, issues with family support, protracted treatment phase, numerous clinic appointments, and illness relapse. 17 …”
Section: Introductionmentioning
confidence: 99%
“…15,16 Other ancillary unaddressed factors may involve economic strains, issues with family support, protracted treatment phase, numerous clinic appointments, and illness relapse. 17 Despite all the powerful technologies and strong targeted medications for cancer patients which are very costly and associated with lethal side effects, the desired success still remains elusive for modern medicine. 14 Patients consequently may turn to nonconventional treatments such as complementary and alternative medicine (CAM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efunkoya et al [ 69 ] reported QoL in patients after oral cancer surgical treatment using the QoL University of Washington (UW-QoL) questionnaire. The UW-QoL is a 15-item questionnaire evaluating problems related to oral function, orofacial appearance, and social interaction.…”
Section: Introductionmentioning
confidence: 99%